1994
DOI: 10.1103/physrevb.49.678
|View full text |Cite
|
Sign up to set email alerts
|

Theory ofp-wave pairing in a two-dimensional Fermi gas

Abstract: The specific heat and susceptibility data for 3 He on Grafoil are analyzed in the framework of the Landau Fermi liquid theory. The dominant interaction between 3 He quasiparticles is found to be in the p-wave channel for most experimentally accessible areal densities of 3 He. This interaction is attractive and gives rise to the p-wave transition temperature which for moderate areal densities is estimated to be on the scale of several millikelvin. The relevance of these results to the anomaly in the specific he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…At higher temperatures, the QNLsM exhibits a crossover to the so-called quantum critical (QC) region, where the proximity to the QC point g g c dominates the behavior [6]. For the square lattice S 1͞2 system the crossover is predicted to be around T ϳ J͞2.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…At higher temperatures, the QNLsM exhibits a crossover to the so-called quantum critical (QC) region, where the proximity to the QC point g g c dominates the behavior [6]. For the square lattice S 1͞2 system the crossover is predicted to be around T ϳ J͞2.…”
mentioning
confidence: 94%
“…For low temperatures CHN found that the only effect of the quantum fluctuations is to renormalize the coupling constants. In this renormalized classical region the correlation length j has been calculated to 3-loop order by Hasenfratz and Niedermeyer [4] with the result thatThe structure factor has an almost Lorentzian line shape with an amplitude given by [5] S 0 13.50 3 N 2 0 j 2 T 2 ͑2pr S ͒ 2 .(2)At higher temperatures, the QNLsM exhibits a crossover to the so-called quantum critical (QC) region, where the proximity to the QC point g g c dominates the behavior [6]. For the square lattice S 1͞2 system the crossover is predicted to be around T ϳ J͞2.…”
mentioning
confidence: 99%
“…In this way F a 0 can be determined with precision. The relative density dependence of F a 0 and F s 1 found experimentally [60], can be compared with the predictions of microscopic theory [47], and we find that both s-wave and p-wave scattering are essential to explain results, such that back-scattering dominates.…”
Section: He 2d Fermi Liquidmentioning
confidence: 68%
“…the system can be tuned through a Feshbach resonance, absent for 2D interactions). Thus 3 He provides an interesting model system to explore interactions in 2D, of significant interest theoretically [44][45][46][47][48][49]. This is important in the wider context of: two dimensional/interface superconductivity in metals [50], incuding FeSe/STO [51], Li/graphene [52,53]; cold atoms, experiments on multiple quasi-2D layers [54,55].…”
Section: He 2d Fermi Liquidmentioning
confidence: 99%
“…The strictly 2D limit corresponds to k −1 F ∼ D ≪ 0 , where 0 = h F ∕2 k B T c is the zero temperature coherence length and D is the film thickness. The 2D superfluidity of a 3 He monolayer has been discussed theoretically in [117][118][119][120][121][122]. In the case of p-wave pairing, this will be sensitive to non-magnetic disorder and requires high-quality substrates.…”
Section: Superfluid 3 He Filmsmentioning
confidence: 99%